2014
DOI: 10.1111/ecog.00662
|View full text |Cite
|
Sign up to set email alerts
|

Spatial synchrony in stream fish populations: influence of species traits

Abstract: International audienceSpatial synchrony in population dynamics has been identified in most taxonomic groups. Numerous studies have reported varying levels of spatial synchrony among closely-related species, suggesting that species' characteristics may play a role in determining the level of synchrony. However, few studies have attempted to relate this synchrony to the ecological characteristics and/or life-history traits of species. Yet, as to some extent the extinction risk may be related to synchrony pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 70 publications
8
41
0
Order By: Relevance
“…Ours is the first study to show that the distance at which dispersal most strongly produces time‐lagged population synchronization is correlated with empirical estimates of dispersal distance. This contributes to our understanding of the mechanisms driving population synchrony, adding to the growing body of literature suggesting that dispersal can synchronize populations (e.g., Chevalier et al, ; Paradis et al, ). These results also provide indirect support for Bearup, Petrovskii, Blackshaw, and Hastings (), who suggested that environmental effects on population synchrony could be distinguished from dispersal effects on population synchrony because the former cause unlagged synchrony, whereas the latter cause time‐lagged synchrony.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Ours is the first study to show that the distance at which dispersal most strongly produces time‐lagged population synchronization is correlated with empirical estimates of dispersal distance. This contributes to our understanding of the mechanisms driving population synchrony, adding to the growing body of literature suggesting that dispersal can synchronize populations (e.g., Chevalier et al, ; Paradis et al, ). These results also provide indirect support for Bearup, Petrovskii, Blackshaw, and Hastings (), who suggested that environmental effects on population synchrony could be distinguished from dispersal effects on population synchrony because the former cause unlagged synchrony, whereas the latter cause time‐lagged synchrony.…”
Section: Discussionmentioning
confidence: 81%
“…Prior empirical studies have found that the average strength of synchrony between populations increases with species dispersal ability (Chevalier, Laffaille, & Grenouillet, ; Paradis, Baillie, Sutherland, & Gregory, ). However, to our knowledge the hypothesis that time‐lagged population synchrony is strongest at the distances a species typically disperses has not been well tested.…”
Section: Introductionmentioning
confidence: 99%
“…However, these were for “periodic” species (optimising fecundity at the expense of the other two traits), which are poorly represented in wadeable streams because they are large‐bodied and require predictable variations in abiotic conditions (Mims & Olden, ; Olden & Kennard, ). Chevalier et al () found that recruitment of opportunistic strategists (i.e. early maturing serial spawners with small clutch sizes) was more correlated than other life‐history strategists.…”
Section: Discussionmentioning
confidence: 99%
“…life history and dispersal) that have been shown to affect other ecological process such as recruitment synchrony (e.g. Chevalier et al, ) and community structure (e.g. de Bie et al, ), but are yet to be examined for spatial patterns of stream fish abundance.…”
Section: Introductionmentioning
confidence: 99%
“…While dispersal could explain differences in degrees of synchrony among distinct species (Chevalier et al, 2014), it seems more likely to bring populations into synchrony at a local scale than at a regional scale (Sutcliffe, While dispersal could explain differences in degrees of synchrony among distinct species (Chevalier et al, 2014), it seems more likely to bring populations into synchrony at a local scale than at a regional scale (Sutcliffe, …”
Section: River Distance Among the Different Sites Did Not Explain Smentioning
confidence: 99%